Determining student progression rates using discrete-time Markov chain model - T. Mangsat, Mark John; A. Garcia, Daniel Bezalel; M. Jacobe, Andhee; A. Bongolan, Maricel (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aims to analyze and understand the student progression from the Bachelor of Science in Mathematics (BS Math) program. A discrete-time Markov chain (DTMC) model was used to analyze data from 211 students enrolled from 2011-2012 to 2022-2023. The results reveal that there are students who will be retained in their year level, shift to another degree program, or drop. Additionally, the highest risk of shifting or dropping out of the program happens during the first two semesters in college or for first year in college. A bottleneck effect during the second year and third year was identified. Furthermore, the results suggest that there will be an approximately 35.22% graduation rate after eight semesters or four years, implying a large portion of BS Math students will be retained or dropped from the program, or shifted to other degree programs. To avoid such, it is suggested that the Mathematics and Natural Sciences Department should conduct review sessions, bridging programs, and continuous promotion. Lastly, it is suggested to conduct thorough studies about the possible intrinsic and extrinsic factors affecting the student progression to formulate a more specific intervention that may help in reducing the shifting and dropping rate.